Danggui Buxue Decoction enhances the anticancer activity of gemcitabine and alleviates gemcitabine-induced myelosuppression. (12th June 2021) - Liu, Yan; Chang, Ming; Hu, Zhaoliang; Xu, Xin; Wu, Wei; Ning, Manru; Hang, Taijun; Song, Min
Abstract: Ethnopharmacological relevance: Danggui Buxue Decoction (DBD) as a traditional Chinese medicine (TCM) has been widely used to treat blood deficiency. With the immune regulation and hematopoietic effect, DBD improved the quality of life in non-small-cell lung cancer (NSCLC) patients. We previously reported that DBD sensitized the response of NSCLC to Gemcitabine (Gem); however, the synergism and attenuation mechanism on the combination of Gem and DBD has not yet been elucidated. Aim of the study: To investigate the mechanisms of DBD in enhancing the anticancer activity of Gem and alleviating Gem-induced myelosuppression. Materials and methods: A549 nude mice model was established to study the effect on the combination of Gem and DBD. The organ indices, peripheral blood cells and the hematopoiesis-related cytokines were analyzed in Gem-induced myelosuppressive mice. Then we studied the whole process from Gem-induced bone marrow suppression to self-healing, and the mechanism of DBD's attenuation by the experiments of bone marrow nucleated cells (BMNCs). Results: There were an enhanced anticancer effect and an improvement of hematopoietic function by combining of Gem and DBD in A549 nude mice model. DBD regulated Hu antigen R (HuR), deoxycytidine kinase (dCK) and nuclear factor erythroid 2-related factor (Nrf2), increased the expression of thrombopoietin (TPO) and granulocyte-macrophage colony stimulating factor (GM-CSF). For Gem-induced myelosuppressive mice, DBD improved the number of peripheral blood cells and the levels of hematopoiesis-related cytokines. Moreover, DBD was observed to reduce deoxyribonucleic acid (DNA) content at the G1 phase, promoted BMNCs proliferation and up-regulated cycle-related proteins. Conclusions: The results indicated that DBD not only improved the sensitivity of Gem but also alleviated Gem-induced myelosuppression. This study may provide a pharmacological basis for the combination of DBD and Gem in clinical application. Graphical abstract: Image 1 Highlights: The combination of Gem and DBD has enhanced anticancer effect and improved the hematopoietic function. Danggui Buxue Decoction improved the sensitivity of gemcitabine through regulating the expressions of Hu antigen R (HuR), deoxycytidine kinase (dCK), nuclear factor erythroid 2-related factor (Nrf2). For the first time, we studied the whole process from gemcitabine-induced bone marrow suppression to self-healing, and the mechanism of Danggui Buxue Decoction's attenuation. Danggui Buxue Decoction alleviated gemcitabine-induced myelosuppression via promoting cell cycle transformation and regulating cycle-related proteins in bone marrow nucleated cells.